2020
DOI: 10.1111/pbr.12860
|View full text |Cite
|
Sign up to set email alerts
|

ATG genes, new players on early Fe toxicity response in rice (Oryza sativa)

Abstract: Rice is a staple food for more than half of the world's population and is directly associated with food security. An additional 100 million tonnes of rice production is estimated to be needed to meet the demand of 9.1 billion people by 2050 (Jaggard, Qi, & Ober, 2010; Mahender, Swamy, Anandan, & Ali, 2019). However, the genetic gain for rice grain yield has stagnated over the past decade, resulting in productivity plateaus even in favourable environments. Also, rice growth and development faces different abiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…Some WRKY TFs are involved in the Fe toxicity response in rice ( Ricachenevsky et al, 2010 ; Finatto et al, 2015 ; Viana et al, 2017 ). WRKY transcription factors are also involved in transcriptional regulation of OsATG (autophagy-related) genes under Fe toxicity, and W-box CREs targeted by WRKY TFs are enriched in the promoters of OsATG genes ( Maltzahn et al, 2020 ). They suggested these genes are involved in the early Fe toxicity response and may be regulated via WRKY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some WRKY TFs are involved in the Fe toxicity response in rice ( Ricachenevsky et al, 2010 ; Finatto et al, 2015 ; Viana et al, 2017 ). WRKY transcription factors are also involved in transcriptional regulation of OsATG (autophagy-related) genes under Fe toxicity, and W-box CREs targeted by WRKY TFs are enriched in the promoters of OsATG genes ( Maltzahn et al, 2020 ). They suggested these genes are involved in the early Fe toxicity response and may be regulated via WRKY.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that CREs related to auxin-responsive element and ABA-responsive elements are present. Maltzahn et al (2020) reported that the promoters of rice autophagy-related genes (OsATG) are rich in W-box CREs that bind WRKY transcription factors, suggesting the possible involvement of these genes in the early response to Fe toxicity. However, the specific and core CREs in promoter sequences that coordinate the expression of most Fe excess-responsive genes in rice remain unknown.…”
Section: Introductionmentioning
confidence: 99%